Increased peroxidase activity associated with resistance to Xanthomonas campestris pv. pruni in inoculated peach (Prunus persica) leaves - Labuschagné, Iwan Frederick (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1994.